Pilocarpine-Induced Status Epilepticus Is Associated with Changes in the Actin-Modulating Protein Synaptopodin and Alterations in Long-Term Potentiation in the Mouse Hippocampus - Maximilian Lenz; Marina Ben Shimon; Thomas Deller; Andreas Vlachos; Nicola Maggio (Neural Plasticity)
Epilepsy is a complex neurological disorder which can severely affect neuronal function. Some patients may experience status epilepticus, a life-threatening state of ongoing seizure activity associated with postictal cognitive dysfunction. However, the molecular mechanisms by which status epilepticus influences brain function beyond seizure activity remain not well understood. Here, we addressed the question of whether pilocarpine-induced status epilepticus affects synaptopodin (SP), an actin-binding protein, which regulates the ability of neurons to express synaptic plasticity. This makes SP an interesting marker for epilepsy-associated alterations in synaptic function. Indeed, single dose intraperitoneal pilocarpine injection (250 mg/kg) in three-month-old male C57BL/6J mice leads to a rapid reduction in hippocampal SP-cluster sizes and numbers (in CA1 stratum radiatum of the dorsal hippocampus; 90 min after injection). In line with this observation (and previous work using SP-deficient mice), a defect in the ability to induce long-term potentiation (LTP) of Schaffer collateral-CA1 synapses is observed. Based on these findings we propose that status epilepticus could exert its aftereffects on cognition at least in part by perturbing SP-dependent mechanisms of synaptic plasticity.